Biomechanical Investigation Between Rigid and Semirigid Posterolateral Fixation During Daily Activities: Geometrically Parametric Poroelastic Finite Element Analyses - Nikkhoo, Mohammad; Lu, Meng-Ling; Chen, Wen-Chien; Fu, Chen-Ju; Niu, Chi-Chien; Lin, Yang-Hua; Cheng, Chih-Hsiu (Frontiers in Bioengineering and Biotechnology, 2021)
While spinal fusion using rigid rods remains the gold standard treatment modality for various lumbar degenerative conditions, its adverse effects, including accelerated adjacent segment disease (ASD), are well known. In order to better understand the performance of semi-rigid constructs using Polyetheretherketone (PEEK) in fixation surgeries, the objective of this study was to analyze the biomechanical performance of PEEK versus Ti rods using a geometrically patient-specific poroelastic finite element (FE) analyses. Ten subject-specific pre-operative models were developed and the validity of the models was evaluated with previous studies. Further, FE models of those lumbar spines were regenerated based on post-operation images for posterolateral fixation at L4-L5 level. Biomechanical responses for instrumented and adjacent intervertebral discs (IVDs) were analyzed and compared subjected to static and cyclic loading. The pre-operative model results were well comparable with previous FE studies. The PEEK construct demonstrated slightly increased range of motion (ROM) at the instrumented level, but decreased ROM at adjacent levels, as compared to the Ti. However, no significant changes were detected during axial rotation. During cyclic loading, disc height loss, fluid loss, axial stress, and collagen fiber strain in the adjacent IVDs were higher for the Ti construct when compared to intact and PEEK models. Increased ROM, experienced stress in AF, and fiber strain at adjacent levels were observed for Ti rod group compared to intact and PEEK rod group, which can indicate the risk of ASD for rigid fixation. Similar to the aforementioned pattern, the disc height loss and fluid loss were significantly higher at adjacent levels in Ti rod group after cycling loading which alter the fluid-solid interaction of the adjacent IVDs. This phenomenon debilitates the damping quality, which results in disc disability in absorbing the stress. Such finding may suggest the advantage of using semi-rigid fixation system to decrease the chance of ASD.